A statistical shape analysis of the neurocranium and long bones - Maass, Petra (Department of Human Biology, 2017)
Morphological variation of skeletal elements, and the potential use of such variation in distinguishing among demographic groups, is often investigated using traditional metric or non-metric assessments. Traditional approaches, however, often fail to sufficiently capture the "true" shape of features, thus also failing to identify potentially important feature characteristics. The development of geometric morphometrics has allowed more comprehensive and accurate three-dimensional data capture which maintains the geometric properties of an object while isolating the effect of size from the data. The aim of this study was to employ the geometric morphometric approach to a 3D digitized sample of 1132 South African individuals from the skeletal collections of the Universities of Cape Town, Stellenbosch, Witwatersrand and Pretoria. Morphological variation among demographic groups was assessed using Generalized Procrustes Analyses applied to the individual bones of the neurocranium and the long bones of the limbs. The ability to distinguish groups based on the detected variation was assessed using Discriminant Function Analysis. The results show that, when size is isolated from the data, only a few elements show sexual dimorphism, while all examined elements show high accuracy in distinguishing among ancestry groups (>74%). When variation is assessed using both parameters, classification accuracies of 70-83% are obtained. Comparison of the different elements shows that the best classification accuracies are based on the frontal bone (84% average) and the humerus (81% average). This study shows that the morphologies of the neurocranium and long bones vary among sex and ancestry groups. This allows assessment of how the combination of variable intrinsic and extrinsic influences can manifest on different parts of the skeleton. In a population as genetically and historically complex as that of South Africa, understanding of the impact of such influences may inform forensic assessments of skeletal material, which is especially valuable considering the high rate of violent crimes and increasing number of unidentified remains being discovered in the country.